Ethnic identity negotiation among Sami youth living in a majority Sami community in Norway - Nystad, Kristine; Spein, Anna Rita; Balto, Asta Mitkijá; Ingstad, Benedicte (International Journal of Circumpolar Health, 2017)
Source at https://doi.org/10.1080/22423982.2017.1316939 . Background: This study was part of the international research project “Circumpolar Indigenous Pathways to Adulthood” (CIPA). Objectives: To explore ethnic identity negotiation, an unexplored theme, among indigenous North Sami youth living in a majority Sami community context in Arctic Norway. Methods: A qualitative design was followed using open-ended, in-depth interviews conducted in 2010 with 22 Sami adolescents aged 13–19 years, all reporting Sami self-identification. Grounded theory, narrative analysis, theories of ethnic identity and ecological perspectives on resilience were applied in order to identify the themes. Findings: All 22 youth reported being open about either their Sami background (86%) and/or ethnic pride (55%). Ethnic pride was reported more often among females (68%) than males (27%). However, a minority of youth (14%) with multi-ethnic parentage, poor Sami language skills, not having been born or raised in the community and with a lack of reindeer husbandry affiliation experienced exclusion by community members as not being affirmed as Sami, and therefore reported stressors like anger, resignation, rejection of their Sami origins and poor well-being. Sami language was most often considered as important for communication (73%), but was also associated with the perception of what it meant to be a Sami (32%) and “traditions” (23%). Conclusion: Ethnic pride seemed to be strong among youth in this majority Sami context. Denial of recognition by one’s own ethnic group did not negatively influence ethnic pride or openness about ones’ ethnic background, but was related to youth experience of intra-ethnic discrimination and poorer well-being. As Sami language was found to be a strong ethnic identity marker, effective language programmes for Norwegian-speaking Sami and newcomers should be provided. Language skills and competence would serve as an inclusive factor and improve students’ well-being and health. Raising awareness about the ...